By His Excellency Thomas Chittenden ... A proclamation : ... to set apart ... and appoint Thursday the twenty ninth day of November next, to be observed as a day of public thanksgiving through this state ... Given under my hand in the Council chamber at Newbury, this 12th day of October in the year of our Lord one thousand seven hundred and eighty seven (1787)
October 12, 1787 Proclamation by Governor Thomas Chittenden setting November 29th as a day of day of public thanksgiving throughout the state for God's goodness and grant of good health.